Literasi Fisik: Analisis Pemahaman Mahasiswa Angkatan 2021 Pendidikan Jasmani Universitas Lambung Mangkurat - Basir, M.; Rakhman, Arie; Rahmadi (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze the understanding of students of the Physical Education Study Program, Class of 2021, Lambung Mangkurat University, regarding the concept of physical literacy and its five main indicators, namely motivation, self-confidence, physical competence, knowledge, and responsibility. Quantitative descriptive method The population studied were students of the 2021 intake of the Physical Education Study Program, Lambung Mangkurat University. The sample in this study was 108 Physical Education students from the 2021 intake of Lambung Mangkurat University. Questionnaire instruments with data analysis techniques using percentage formulas are often applied to understand the proportion or distribution of data based on certain categories. The motivation indicator is very good with a percentage of 51.02%, the self-confidence indicator is good with a percentage of 50.93%, the physical competence indicator is good with a percentage of 53.52%, the knowledge is good with a percentage of 60.00%, and the responsibility is good with a percentage of 55.29%. The conclusion of this study is that the results are good with a percentage of 53,05%.